Analisis Fenomena Childfree dalam Hukum Fiqih Islam (Studi Pendekatan Konsep Niat) - Fauzi, Irfan; Salamah, Daris; Anwar, Zaeni; Apni, Cut Nadila (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The phenomenon of childfree, which is the decision not to have children, has become an increasingly discussed topic in Indonesia, especially along with the influence of feminism and liberalism movements from the West. This study aims to analyze the phenomenon of childfree from the perspective of the concept of intention in Islam, in order to determine its legal status. Using the descriptive analysis method, this research highlights the importance of intention and the methods used in the practice of childfree. In Islam, intention plays a crucial role in determining the value of an action. The decision not to have children is acceptable if it is based on intentions that are in accordance with Sharia and the methods used do not contradict Islamic principles. For example, if a couple chooses not to have children due to health reasons that could endanger one of the parties, or due to considerations of greater benefit, then the decision can be justified. Conversely, if the decision is based on intentions that are not in accordance with Islamic teachings, such as unwillingness to fulfill the role of parents without justified reasons, then the practice of childfree becomes impermissible. This research confirms that the determination of the law regarding childfree should consider the intention underlying the decision and the method used. Thus, it is important for individuals and couples to understand and evaluate their intentions in the context of Islamic teachings before deciding not to have children. The results of this study are expected to provide insight for the community to be wiser in addressing the phenomenon of childfree, as well as emphasizing the importance of intention and methods that are in accordance with Sharia in every decision taken.